Study of molar properties of GO after doping with transition metals for photodegradation of fluorescent dyes. Issue 46 (18th October 2022) - Kumar, Krishan; Dave, Riddhi P.; Dev, Sachin; Singh, Man
Abstract : We synthesize and characterise graphene oxide doped with transition metal ions, and calculate the Mark–Houwink constants, determining methylene blue degradation efficiency. Abstract : We synthesized graphene oxide (GO) doped with transition metal ions and characterized it using XPS, FT-IR, TGA/DTG, XRD, SEM, AFM, ICP-OES, UV/vis, and Raman spectroscopy. An intrinsic viscosity [ η ] of 0.002–0.012 g% @ 0.002 aq-GO was determined for viscosity average molecular weight ( M v ) of GO at 288.15, 298.15, and 308.15 K. Mark–Houwink (M–H) constants k (cm 3 g −1 ) and a (cm 3 mol g −2 ) were calculated for 5–15 mg/100 mL polyvinylpyrrolidone (PVP), using 29, 40, 55 kg mol −1 as markers for calculating M v by fitting the [ η ] to the Mark–Houwink–Sakurada equation (MHSE). We obtained 48 134.19 g mol −1 M v at 298.15 K, and the apparent molar ( V ϕ m, cm 3 mol −1 ), limiting molar volumes ( V 0GO)GO⃑0, enthalpy (Δ H m, J mol −1 ), entropy (Δ S m, J mol −1 K −1 ), viscosity ( η m, mPa s mol −1 ), surface tension ( γ m, mN m −1 mol −1 ), friccohesity ( σ m, scm −1 mol −1 ), fractional volume ( ϕ m, cm 3 mol −1 ), isentropic compressibility ( K sϕ, m, 10 −4 cm s 2 g −1 mol), infer GO molar consistency throughout the chemical processes. Molar properties (MPs) infer a GO monodispersion producing negative electrons (e − ) and positive holes (h + ) under sunlight. The transition metal ions (Fe 2+, Mn 2+, Ni 2+, Cr 3+, TMI) doped onto GO (TMI-GO), can photodegrade methylene blue (MB) in 60 min compared with 120 min using GO alone. The 4011 C atoms, 688 hexagonal sheets, 222 π-conjugations, and 4011 FE were calculated from the 48 134.19 g mol −1 . The functional edges are the negative and positive holes generating centres of the GO 2D sheets.